Factorise
(m+1)Square -9
My answer : (m-8)(m+8)
And also, is it true that we can't write capital letters for algebra? only small letters.
Thanks so much for helping!
Factorise
(m+1)Square -9
My answer : (m-8)(m+8)
And also, is it true that we can't write capital letters for algebra? only small letters.
Thanks so much for helping!
That would be m*m+ m*8-8*m- 8*8 and since "m*8" and "8*m" are the same thing m*8- 8*m= 0 and that is m^2- 8 ^2= m^2- 64.
Instead, you should have (m+ 1)^2= (m+1)(m+1)= m*m+ m*1+ 1*m+ 1*1= m^2+ m+ m+ 1= m^2+ 2m+ 1. Now subtract the 9.
No, that is not true. What is true, and, I suspect, what you were told, is that small and capital letters are NOT interchangeable. You can have "A" and "a" but they mean different things because they are different symbols. Unless you have a good reason, it would be a bad idea to use both "A" and "a" in the same formula, since people would not be sure if you intended them to mean the same thing or not. But you have problem seen formulas such as "A= hw" or "A= (1/2)bh" for area.And also, is it true that we can't write capital letters for algebra? only small letters.
Thanks so much for helping!
Yes, that is correct.
Since both Unknown008 and I have already told you that is NOT correct, why are you repeating it? I told you before that (m- 8)(m+ 8)= m*m+ m*8- 8*m- 8*8= m^- 8*8= m^2- 64 NOT m^2+ 2m- 8.So using the formula above, answer is (m-8)(m+8)?
If a and b are any two numbers, then (m- a)(m+ b)= m*m+ m*b- a*m- ab= m^2+ (b- a)- ab. You want that to be the same as m^2+ 2m- 8. That is, you want b- a= 2 and ab= 8. You want two numbers whose difference is 2 and whose product is 8. What whole number factors does 8 have?
Please enlighten me
If a is m, and b is 4...
$\displaystyle m^2 +2m-8$
How can you replace m by a and 4 by b here?
Like this?
$\displaystyle a^2 +2a-2b$
This doesn't bring to (a-b)(a+b)
Like this?
$\displaystyle a^2 +\dfrac{ba}{2}-\dfrac{b^2}{2}$
That neither.
In short, no. If you ever got $\displaystyle m^2 - 9$ for example, then it would be $\displaystyle m^2 - 9 = (m+3)(m-3)$. But that is not the case.